REGISTER PERTANIAN PADA MASYARAKAT DESA BANGKAL KOTA BANJARBARU - Islamiati Normalida; Noor Indah Wulandari (STILISTIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
ABSTARACK This study examines the register in a profession, namely agriculture. The aims of this study were to: (1) describe theform of agricultural registers in Bangkal village, (2) describe the meaning and function of agricultural registers in Bangkal village, (3) describe the causesof agricultural registers in Bangkal village. The approach used in this research is a qualitative approach with a qualitative descriptive type of research. A qualitative approachis an approach that us carried out without systemtic calculations. This approach intend to understand the phenomeno of what is experienced by the object of research. the qualitative approach is an attemp to understand other linguistic phenomena being studied. While the type of qualitative descriptiveresearch is an activity to obtain resultthat are as they are, without being manipulated, without engineering, the result of wich emphasize more on meaning. The subjects in this study were farmers inBangkal village, witha total of 4 informants. the conclusions of this study are (1) the formof the agricultural register in the Bangkal village community, Banjarbaru City, includes 35 vocabulary words, 4 vocabularies in phrase form, (2) the meaningof agricultural registers in the Bangkal village community, Banjarbaru city includes lexical meaning. The meaning of the register refers to speakers who use it in agricultural, and the function of the vocabulary. For example, harit serves as a tool for cutting rice, ranggaman serves as a tool for picking rice stalks when harvesting, tatujah serves as a tool for making holes when planting rice. in addition to the function of the vocabulary itself, this agricultural register also has functions as languange fungction, and personality function, (3) the causes of agricultural registersin the Bangkal village community, namely work factors, habits, and social factors.